Characterization of Arsenite Resistant Escherichia coli Isolated from Tubewell Water of Singair, Manikganj, Bangladesh - Sanyal, Santonu Kumar; Chakrabarty, Ram Prosad; Hossain, M Anwar; Sultana, Munawar (Bangladesh Journal of Microbiology, 2016)
Arsenic is a toxic metalloid present in the natural environment and arsenite is more toxic form than arsenate. Bacterial species have evolved multiple defense mechanisms to tolerate and transform the toxic forms of arsenic. In this study, arsenic contaminated tubewell water (90 meter depth with arsenic concentration of 47 ?g/l) was collected from Singair Upazilla under Manikganj District in Bangladesh. Among a total of 17 arsenite resistant bacteria, a lactose fermenting isolate Sn26 showed high resistance to sodium arsenite up to 25 mM under our laboratory conditions. Sn26 possesses arsB gene conferring arsenite transporter pump mediated arsenic resistance, confirmed by PCR and sequencing. PCR and sequencing of 16S rRNA gene (approximately 1450 bp) confirmed Sn26 isolate as Escherichia coli. The isolate contained a large plasmid of ~34 kb. It is necessary to analyze further the affiliation of this single plasmid with high arsenite tolerance. Bangladesh J Microbiol, Volume 31, Number 1-2,June-Dec 2014, pp 13-17